The Difference of the Knowledge, Stigma and Attitude between The First Year and Final Year Student of Medical Faculty of Jember University toward Mental Disorders - Dinda Ayu Teresha; Justina Evy Tyaswati; Kadek Dharma Widhiarta (Journal of Agromedicine and Medical Sciences, 2015)
Mental disorders is one of the health problems in developing countries and developed countries. One of the biggest problems faced by those with mental disorders is the presence of that and negative attitudes due to lack of public knowledge. Several previous studies have found that education increase knowledge and change the stigma and negative attitudes on medical students. The purpose of this study was to analyze the differences of knowledge, stigma and attitude between first year and final year student of the Medical Faculty of Jember University toward mental disorders. This research was a quantitative research with cross sectional approach. The samples were the students class of 2012 and 2014. The independent variable was the class of the students, while the dependent variable was knowledge, stigma, authoritarianism, benevolence, social restrictions, and istatistik of health community. The data was analyzed using chi-square test. Based on the test result, it was found that the variables with a significant difference is stigma (p= 0.001) and authoritarianism (p = 0.025). In conclusion there were significant differences on stigma and attitudes of authoritarianism between the first year and final year students to the mental disorders. Keywords: Stigma, Authoritarianism, Benevolence, Social Restrictiveness, Community Mental Health Istatistik